Clinical and Sonological Evaluation of Borderline Amniotic Fluid Index and Oligohydramnios-Its Correlation with Perinatal Outcomes - Saira Jamsheed; Khadijah Abid (Life and Science, 2024)
Objective: To evaluate the correlation of low borderline amniotic fluid index and oligohydramnios with perinatal outcomes among pregnant females presenting at the tertiary care hospital of Karachi. Study Design: Cross-sectional study. Place and Duration of Study: The study was conducted at the Department of Obstetrics and Gynecology, Hamdard University, Karachi, Pakistan, from March 2021 to March 2022. Methods: Females aged 18-45 years, with a gestational age of 20-42 weeks assessed on the last menstrual period and a single fetus on ultrasound were enrolled. The final sample size for the study was determined to be 260 with 130 participants in each group, i.e., the females with Amniotic Fluid Value (AFI) value of ≤5 cm considered as oligohydramnios (group-1) and AFI value of 5.1 to 8 cm considered as borderline AFI (group-2) The amniotic fluid index value was determined in all the females using ultrasonographic reports by the consultant physicians. Females were classified as having oligohydramnios if their amniotic fluid index value was less than 5 cm and borderline amniotic fluid index between 5.1 and 8 cm. To evaluate the maternal and perinatal outcomes, all females were monitored up to birth. Data was analyzed using SPSS version 23. Results: The mean maternal age was 29.85±5.45 years, and the mean BMI was 29.78±5.62 kg/m . Most of the females had gravida ≥1. Females with oligohydramnios had higher rates of low birth weight (84.6% vs. 51.5%, p=0.001), IUGR (68.5% vs. 22.3%, p=0.001), meconium staining (42.3% vs 7.7%, p=0.001), low APGAR score (50.8% vs. 13.8%, p=0.001), respiratory distress syndrome (72.3% vs 27.7%, p=0.001), birth asphyxia (65.4% vs 23.1%, p=0.001), NICU admission (73.8% vs. 43.1%, p=0.001), and neonatal death (21.5% vs. 5.4%, p=0.001) than women with borderline amniotic fluid index. Conclusion: This observational study demonstrates a significant correlation between oligohydramnios and adverse perinatal outcomes, emphasizing the importance of vigilant monitoring and intervention in pregnancies with low amniotic fluid.